SOSIALISASI MEDIA ALAT PERMAINAN EDUKATIF (APE) UNTUK MENINGKATKAN MOTORIK ANAK MADRASAH IBTIDAIYAH MUHAMMADIYAH CIPUTAT - Muhammad Ishaq Gery; Dewi Setiyaningsih; Imam Mujtaba; Imam Mahfud; Putra Andhika Ali Pratama; Aditya Alhaqiqi (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This community service program aims to promote the use of APE media for children's motor development. Motor skills are fundamental to a child's development, especially for children aged five to ten years, enabling them to develop more fully. This program focuses on children's motor development, which consists of fine and gross motor skills, through the use of simple media, namely APE (Educational Toys). Through this media promotion, it will be possible to assess the extent of children's motor skill development relative to their age. This community service initiative has a specific target: to promote the use of APE media in schools and at home to support the healthy development of children's motor skills, including both fine and gross motor skills. The methods employed include lectures and demonstrations. The results of the data summary table show that the average pre-test score was 52, while the average post-test score was 85.3. The percentage increase in knowledge about children's motor development was 33.3%. From this data, it can be concluded that there was an increase in knowledge about the modification of Educational Toys at MI Muhammadiyah Ciputat.